Seismic performance and SSI effects of a two-storey RC school building during the 2014 Cephalonia, Greece, earthquake sequence - Christos Giarlelis; Constantinos Repapis; Evlalia Lamprinou; George Mylonakis; George Manolis; Anastasios Sextos (Bulletin of Earthquake Engineering, 2023)
The response of a two-storey RC school building in the town of Argostoli, Cephalonia Island, Greece, during the seismic sequence of January and February 2014, is examined. The structure was built following an older generation of seismic codes dating from the 1950s, which provide limited strength and ductility against lateral loads. Despite the severity of ground shaking and the two successive events, the building suffered relatively minor damage, like most of the RC buildings in the town. Following a short presentation of some basic seismological, structural and geotechnical aspects of the seismic sequence, the paper focuses on the seismic performance of the structure at hand. To this end, a series of detailed non-linear static and time-history dynamic analyses are reported, which highlight the interplay of soil, foundation and superstructure in modifying the seismic demand. It is demonstrated that SSI had an unexpectedly important (detrimental) role in the behaviour of the structure, increasing its natural period by about 25% and aggravating ductility demand in almost all columns, despite the moderately soft soil conditions (average V S = 180 m/s). The results shed light on the seismic performance of the building and help drawing conclusions on the engineering effects of the 2014 Cephalonia earthquake sequence.